Workforce Localization in the Arab Gulf Countries: How Do Organizations Socialize the Members of a Powerful Minority? - Waxin, Marie-France (2020)
This paper addresses a key social–cultural aspect of sustainability in the Gulf region: Workforce localization (WL). Our research objective is to empirically explore organizational socialization (OS) practices in the context of WL in the United Arab Emirates (UAE), where National Citizens (NCs) are a powerful minority in the workforce. This research adopts a qualitative methodology, using semi-structured interviews with managers in charge of the WL program in 14 organizations in the UAE, across different industrial sectors and ownership. We found five major OS practices: Establishing thorough orientation programs, providing formal training programs (skills, diversity/cultural awareness, supervisor, mentoring and coaching team building), redesigning NCs' jobs and work teams, engaging expatriates in NCs' OS processes, and organizing networking events. All organizations rigorously evaluated the effectiveness of their OS practices. This study contributes to the empirical literature on management OS, WL, and diversity management in a non-western, emerging Arab country. It contributes to theory development on the content of OS practices, showing how a minority can be a powerful group around whom socialization processes are tailored to integrate them fully into the organization. Practically, our findings inform managers of how to adapt their existing OS practices to the specific needs of minority members, and support Gulf Cooperation Council (GCC)-based organizations and policymakers with the design, monitoring, and implementation of WL programs, and with the development of a sustainable workforce.